Perception of Distance Learning: Results of Surveys of Students and Faculty - Temerbulatova, Zhansaya; Kondybayeva, Saltanat; Boluspayev, Shalkar; Kaliyeva, Assem; Salibekova, Perizat (Emerging Science Journal, 2025)
The study aims to evaluate the impact of distance learning on the quality of higher education from the perspectives of students and faculty, focusing on satisfaction, academic performance, and perceptions of digital education. To achieve this, quantitative data were collected through two online surveys of students and faculty from 25 universities across Kazakhstan. Statistical methods, including the Mann–Whitney U Test, ANOVA, Correlation Analysis, Chi-Square Test, and Descriptive Statistics, were applied to test nine hypotheses. The results revealed that graduate students generally perceive distance learning more positively than undergraduates, while both groups identified technical difficulties and reduced personal interaction as the main barriers. A moderate positive correlation was found between student satisfaction and academic performance, indicating that interactive and well-structured online environments enhance learning outcomes. Faculty members reported increased stress and workload, highlighting the need for better institutional support and digital infrastructure. The novelty of this study lies in its comprehensive comparative assessment of both students’ and teachers’ experiences in the context of Kazakhstan’s higher education system, offering valuable practical recommendations for improving hybrid and online learning models and ensuring their long-term effectiveness in post-pandemic conditions.